Sodium N-lauryl amino acids derived from silk protein can form catanionic aggregates with cytarabine as novel anti-tumor drug delivery systems - Meng Zhang; Shu-Xiang Zhao; Biao Ding; Yu-Qing Zhang (Taylor & Francis Group, 2020)
A sodium N-lauryl amino acids (shortly silk sericin surfactant, SSS) is synthesized with lauryl chloride and sericin amino acids recovered from silk industrial waste. The purpose of this study is to explore whether the sericin surfactant can be used as a potential drug delivery carrier. By controlling the proportion of cationic drugs, cytarabine hydrochloride (CH) and anionic SSS, the aggregation behavior, slow release capability and toxicological effects of catanionic aggregates or vesicles, formed through CH and SSS, have been investigated in detail. Dynamic light scattering (DLS), transmission electron microscopy (TEM), and zeta potential analysis showed that the aggregate solution could form a stable vesicle structure when the mass fraction of CH is less than or equal to 0.3. The drug release results showed that the cumulative release rate of the catanionic aggregation solution with CH mass fraction of 0.2 reached a maximum at 18 h, being approximately 9 times greater than that of pure cytarabine. The CH/SSS aggregates had a significant sustained release effect compared with the control group. At the same time, vesicles formed by SSS and CH have better anti-tumor effects compared with the pure drug group. In summary, sericin surfactant from silk industrial waste has a potential use as a drug delivery carrier.